ETHNOGRAPHIC DESCRIPTION OF SACRED AND PILGRIMAGE PLACE OF KASHKADARYA OASIS - Rakhmonov Fakhriddin Shoymardonovich (Scholars Digest Publishing, 2023)
In the current era of globalization, the integration of civilizations and the understanding of the national identity of peoples and the preservation of local cultures are becoming a priority. This requires a deep scientific study of the objects of cultural heritage in different historical and ethnographic regions as the basis of folk culture. There are more than 600,000 historical and archeological monuments, museums and other institutions in the world, 750 of which are included in the list of world cultures. The article describes the ethnographic description of the shrines and shrines of the Kashkadarya oasis, as well as provides recommendations on the classification of shrines, the rules of pilgrimage.
Keywords: Uzbekistan, Oasis of Kashkadarya, Independence, Sacred premise, Ethnographic details, historical architecture, tourisim of sacred places, tourisim of ethnological places, historical-administrative memories.